A adoção das licitações sustentáveis nas Companhias Docas do Brasil e sua prática na Companhia Docas do Espírito Santo - Falcão, Maria Elisa de Freitas (2017)
The sustainable procurement is created by including sustainable criteria in the documents that compose a bidding, consisting in a mechanism to promote the sustainable development. The basis of its existence is on Chapter 4 of Agenda 21 and for its adoption there is the Normative Instruction N°. 01/2010. Its application is extended for all public agencies and companies, including public ports, which have a large influence on the national economy, so identify instruments and criteria used, its effectiveness and possibilities for improvementcan contribute for the theme comprehension. Therefore, were made researching in Dock Companies websites; analyzing the published bidding notices in 2015; interviews; and case study of Dock Company of Espírito Santo (Codesa). Of eight Companies investigated, five have regulation and only three made it available in their websites. Also five made their bidding notices available in their website, which analysis pointed that the majority of sustainable criteria researched presents low representativity, except the requirement of not hiring employees under the age of 18. At the interviews, conducted in seven Companies, the legal sectors and the Bid Committees was appointed by all of them as responsible for elaborating the bids. About the internal regulation, two have affirmed to have it, three that it is in development and two that there is nothing on it. The case study demonstrated that the internal regulation proposes criteria for various types of product acquisition and contracting services; and the interviews pointed that was not offered any training about the theme and that the main barriers are the lack of commitment of the senior management and the lack of environmental awareness of the employees. Thus, there is in terms of the current state of sustainable procurements in port sector, the level of adherence is good, but the level of effective implementation is low. To improve its adherence it is required an internal regulation that regulates the inclusion of sustainable criteria containing responsibility attributions, being well publicized and accompanied by training.